SISTEMATIKA PENDAFTARAN HAK ATAS KEKAYAAN INTELEKTUAL (HAKI) DALAM BIDANG PATEN - Elsi Kemala Putri; Jasman Nazar (INTELIGENSIA MEDIA, 2024)
A patent is an exclusive right granted by the state to an inventor for the technological results of his invention. For a certain duration, the patent holder can use the invention itself or can authorize a third party to do so. Modern technology has been incorporated into almost every aspect of life, both domestically and internationally. Therefore, laws related to patents must be established. This law should regulate the terminology and definitions related to patents as well as the conditions, procedures, time frames, modes of protection, rights and obligations of patent holders, licenses, expiration of licenses, royalties, and other issues. In order to give inventors legal protection, this is utilized as a guide when conducting patent-related operations in Indonesia. Protection is required in order to: Encourage them to keep working toward a better future for the country and state; Provide a kind of acknowledgment, assurance, and guarantee grounded in a feeling of fairness and worthiness for all their abilities and efforts. Even though Indonesia has ratified international accords pertaining to patents and already has laws and regulations in place, issues sometimes arise. Numerous elements, such as those pertaining to legal culture, legal content, and legal structure, have an impact on the prevalence of these issues.